2009
DOI: 10.1371/journal.pntd.0000435
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Developing Odour Baits To Control Glossina fuscipes spp., the Major Vector of Human African Trypanosomiasis

Abstract: We are attempting to develop cost-effective control methods for the important vector of sleeping sickness, Glossina fuscipes spp. Responses of the tsetse flies Glossina fuscipes fuscipes (in Kenya) and G. f. quanzensis (in Democratic Republic of Congo) to natural host odours are reported. Arrangements of electric nets were used to assess the effect of cattle-, human- and pig-odour on (1) the numbers of tsetse attracted to the odour source and (2) the proportion of flies that landed on a black target (1×1 m). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 36 publications
2
74
0
Order By: Relevance
“…[49][50][51] and mosquito [52] collections, were trialled as potential replacements of vector collector methods. These traps were used for blackfly collection on sporadic dry days during the rainy season in 2009 and followed up with a full feasibility investigation during a two-week period in August 2010 in the dry season.…”
Section: Host-seeking Blackfliesmentioning
confidence: 99%
“…[49][50][51] and mosquito [52] collections, were trialled as potential replacements of vector collector methods. These traps were used for blackfly collection on sporadic dry days during the rainy season in 2009 and followed up with a full feasibility investigation during a two-week period in August 2010 in the dry season.…”
Section: Host-seeking Blackfliesmentioning
confidence: 99%
“…It is therefore pertinent to summarise briefly the main features of the important Palpalis group species (reviewed in Solano et al 2009). …”
Section: Ecology Of Riverine Fliesmentioning
confidence: 99%
“…Finally, in Congo-Brazzaville, Frezil and Carnevale (1976) showed that baiting a trap with carbon dioxide increased the catch of G. f. quanzensis Pires ~40×. (Omolo et al 2009, Rayaisse et al 2010 suggest that these species show moderate but significant responses to host odours. For instance, studies in Burkina Faso have shown that there is a significant ~1.5× increase in the numbers of G. p. gambiensis attracted to a source of ox odour, and that a blend of acetone, 4-methylphenol, 3-n-propylphenol and octenol can double the catch from traps (IAEA 2003, Rayaisse et al 2010.…”
Section: Other Palpalis Group Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Omolo et al (2009) have studied the responses of this insect to natural host odours by odour baits. Odours of cattle, pig, human and monitor lizard (Varanus niloticus) were used in the experiments.…”
Section: Examples Of the Practical Usage Of Kairomones For The Contromentioning
confidence: 99%